Prospective Longitudinal Study of Putative Agents Involved in Complex Gill Disorder in Atlantic salmon (Salmo salar) - Ana Herrero; Hamish Rodger; Adam D. Hayward; Chris Cousens; James E. Bron; Mark P. Dagleish; Kim D. Thompson (Pathogens, 2022)
Complex gill disorder (CGD) is an important condition in Atlantic salmon aquaculture, but the roles of the putative aetiological agents in the pathogenesis are uncertain. A longitudinal study was undertaken on two salmon farms in Scotland to determine the variations in loads of CGD-associated pathogens (Desmozoon lepeophtherii, Candidatus Branchiomonas cysticola, salmon gill pox virus (SGPV) and Neoparamoeba perurans) estimated by quantitative PCR. In freshwater, Ca. B. cysticola and SGPV were detected in both populations, but all four pathogens were detected on both farms during the marine stage. Candidatus B. cysticola and D. lepeophtherii were detected frequently, with SGPV detected sporadically. In the marine phase, increased N. perurans loads associated significantly (p < 0.05) with increases in semi-quantitative histological gill-score (HGS). Increased Ca. B. cysticola load associated significantly (p < 0.05) with increased HGS when only Farm B was analysed. Higher loads of D. lepeophtherii were associated significantly (p < 0.05) with increased HGS on Farm B despite the absence of D. lepeophtherii-type microvesicles. Variations in SGPV were not associated significantly (p > 0.05) with changes in HSG. This study also showed that water temperature (season) and certain management factors were associated with higher HGS. This increase in histological gill lesions will have a deleterious impact on fish health and welfare, and production performance.